Food Safety Knowledge, Attitude And Hygiene Practices Among The Street Food Vendors In Northern Kuching City, Sarawak - Md Mizanur, Rahman; Mohd.Taha, Arif; Kamaluddin, Bakar; Zainab, Tambi (Borneo Science, 2012)
Street food vending is a prevailing and distinctive part of a large informal sector in both developed and developing countries. Food safety is a key public health concern, because a large number of people take their meals outside the home and are exposed to food borne illnesses. Food handlers play an important role in ensuring food safety throughout the chain of storage, processing production, preparation and retailing. The objective of the study is to assess the level of knowledge, attitude and practice of food safety among the food vendors in Kuching City, Sarawak and to determine the factors affecting them. A cross sectional study was conducted among the street vendors in Kuching City. A total of 361 street food vendors were selected using non-probability sampling technique. Data were collected by face to face interview using a structured questionnaire. All completed questionnaires were validated manually and data analysis carried out by computer using SPSS version 19.0 software package. Multinomial regression analysis revealed that age and ethnicity appeared to be important factors for food safety knowledge (p<0.05), whereas food safety knowledge and training appeared to be influencing factors for attitude (p<0.05). On the other hand, food safety knowledge, attitude, training and age of the food vendors influence the food safety practice, but duration of food vending had an inverse relationship with food safety practice (0<0.05). Findings of this study may help in planning health intervention programs for food handlers for their improvement of knowledge, attitude and practice towards food-borne diseases and food safety. Furthermore, this will in turn reduce the morbidity and mortality of food-borne diseases.